Application of the famacha© system for the evaluation of haemonchosis in small ruminants reared in a communal system of the Molemole Municipality, Limpopo Province, South Africa - Senoamadi, Mashakgene Isaac; Tyasi, Thobela Louis; Chitura, Teedzai (Advances in Animal and Veterinary Sciences, 2022)
The present study was conducted to determine the occurrence of clinical haemonchosis and methods of controlling Haemonchus contortus and other internal parasites in a communal farming system of Limpopo province, South Africa. Twenty-six sheep and one-hundred and sixty-three goats were evaluated for clinical haemonchosis using the FAMACHA© diagnostic system. Information on the methods of control used by the smallholder farmers was gathered through a questionnaire-based survey that was carried out by interviewing forty-seven Small ruminants farmers (both males and females) of mixed ages. The average FAMACHA© score for the goats was three while for sheep the average score was 2.62. Ninety-eight goats (60%) had a FAMACHA© score of three and above while fourteen sheep (52.4%) had a FAMACHA© score of three and above. There was a high occurrence of haemonchosis in goats compared to sheep (p<0.05). Differences in occurrence between age groups, sex and physiological status were found to not be statistically significant in both small ruminants (p>0.05). The methods of internal parasite control used by the smallholder farmers in the study area were commercial anthelmintic drugs (38.3%), ethno-veterinary based methods (12%) while 46.8% did not control gastrointestinal parasites. It can be concluded that clinical haemonchosis presents a potential challenge in the study area due to a low adoption rate of internal parasite control measures among the farmers interviewed.
Journal article published in Advances in Animal and Veterinary Sciences May 2022 | Volume 10 | Issue 5 | Page 1101
Keywords: Anthelmintic; Ethno-veterinary; Gastrointestinal parasites; Haemonchus contortus; Respondents; Haemonchus contortus; Ruminants